Effects of Two Different Bleaching Agents on the Micro Hardness of the Enamel of the Tooth - Muhammad Sidique Qazi, Anny Memon, Ashar Hussain, Ashfaque Ali Arain, Hafiz Mahmood Azam, Afshan Jawaid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Tooth bleaching is widely used for aesthetic enhancement, but it may negatively affect enamel integrity, particularly microhardness. Objective: To evaluate the micro hardness of the enamel of the tooth by comparing two different bleaching agents. Methodology: This experimental in vitro study was conducted over six months using 60 extracted human permanent teeth (100%). Teeth free from caries, structural defects, or prior treatment were randomly divided into two equal groups (n = 30 each), further split into control and experimental subgroups (n = 20 each). One group was treated with 22% carbamide peroxide and the other with 37.5% hydrogen peroxide following standardized protocols. All specimens were stored in artificial saliva between treatments to simulate oral conditions. Enamel microhardness was measured at baseline, 24 hours, 7 days, and 14 days using the Vickers Hardness Test. Data were analyzed using SPSS version 22, with a p-value < 0.05 considered significant. Results: In the carbamide peroxide group, the experimental subgroup showed a reduction in microhardness from 387.775 ± 26.028 initially to 381.375 ± 48.265 on day 7, with partial recovery to 387.575 ± 29.582 by day 14. The hydrogen peroxide group exhibited identical values across all time points. All within-group and between-group comparisons were statistically significant (p = 0.000), though the magnitude of difference was minimal. Conclusion: Both bleaching agents caused a slight, reversible reduction in enamel microhardness, with no significant difference between them under in vitro conditions. Keywords: Tooth bleaching agents, enamel microhardness, carbamide peroxide, hydrogen peroxide, Vickers hardness test.